Reliability and Validity of the Arabic Version of a Questionnaire Assessing Pain, Discomfort and Related Jaw Function Impairment after Extraction of Primary Teeth in Children - Reem Naaman; Azza A. El-Housseiny; Najlaa Alamoudi; Narmin Helal; Rahaf Sahhaf (Dentistry Journal, 2020)
This study aims to translate a previously published English language questionnaire that assessed pain and discomfort after the extraction of primary teeth in children into Arabic, and evaluate its validity and reliability. All participating children (n = 120), aged 9 to 12-years-old, completed the 33-item Arabic version questionnaire after the extraction procedure had taken place. The questionnaire included three parts that were completed at three different times, namely, immediately, the first evening, and one week after the extraction procedure. Internal consistency, content validity, criterion validity, and factor analysis were performed. The results showed a good internal consistency (Cronbach’s alpha = 0.83), acceptable criterion validity with a significantly strong correlation with the Visual Analog Scale (VAS), and satisfactory content validity (average content validity index (CVI = 0.90). The final factor model was comprised of four factors with an eigenvalue greater than 1, explaining 70% of the common variance. The identified factors were labeled as follows: Factor 1—analgesic consumption; Factor 2—expression of discomfort from the extraction site; Factor 3—perception of masticatory capability; and Factor 4—pain/discomfort from the dental extraction procedure. Based on the results, a shorter form of the questionnaire had satisfactory psychometric characteristics and can be used with children within the selected age group.